Integration of In Silico and In Vitro ADMET properties in lead identification and optimization of compounds for the treatment of parasitic diseases - Thelingwani, Roslyn (Department of Chemistry, 2014)
Parasitic infections are the major causes of illness and death in tropical regions especially in Africa. The main parasitic diseases include leishmaniasis, filariasis, malaria, river blindness, Chagas disease and schistosomiasis. With the absence of vaccines, treatment relies mainly on chemotherapy hence the need for efficacious and safe medicines. Many of the medicines currently used have low efficacy and cause side effects. Some are also being lost to drug resistance. To address the inadequacy of treatment options for infectious diseases, a number of initiatives have been started to promote drug discovery and development in Africa. In parallel they have been collaboration between African institutions and leading pharmaceutical companies as well as other relevant R & D organizations. This has led to the need to modernize African approaches to drug discovery and development with respect to the integration of medicinal chemistry, pharmacology and pharmacokinetics as reflected in the processes of Absorption, Distribution, Metabolism, Excretion and Toxicity (ADMET). However, scientific and technological expertise in pharmacokinetics for drug discovery is under developed in Africa.